Role of TGF-β in proliferative vitreoretinal diseases and ROCK as a therapeutic target - Kita, Takeshi (National Academy of Sciences, 2008)
Cicatricial contraction of preretinal fibrous membrane is a cause of severe vision loss in proliferative vitreoretinal diseases such as proliferative diabetic retinopathy (PDR) and proliferative vitreoretinopathy (PVR). TGF-β is overexpressed in the vitreous of patients with proliferative vitreoretinal diseases and is also detectable in the contractile membranes. Therefore, TGF-β is presumed to contribute to the cicatricial contraction of the membranes, however, the underlying mechanisms and TGF-β's importance among various other factors remain to be elucidated. Vitreous samples from PDR or PVR patients caused significantly larger contraction of hyalocyte-containing collagen gels, compared with nonproliferative controls. The contractile effect was strongly correlated with the vitreal concentration of activated TGF-β2 (r = 0.82, P < 0.0001). PDR or PVR vitreous promoted expression of α-smooth muscle actin (α-SMA) and phosphorylation of myosin light chain (MLC), a downstream mediator of Rho-kinase (ROCK), both of which were dramatically but incompletely suppressed by TGF-β blockade. In contrast, fasudil, a potent and selective ROCK inhibitor, almost completely blocked the vitreous-induced MLC phosphorylation and collagen gel contraction. Fasudil disrupted α-SMA organization, but it did not affect its vitreal expression. In vivo, fasudil significantly inhibited the progression of experimental PVR in rabbit eyes without affecting the viability of retinal cells by electroretinographic and histological analyses. These results elucidate the critical role of TGF-β in mediating cicatricial contraction in proliferative vitreoretinal diseases. ROCK, a key downstream mediator of TGF-β and other factors might become a unique therapeutic target in the treatment of proliferative vitreoretinal diseases.